Survival analysis and prognostic factors associated with the timing of first forced sexual act among women in Kenya, Zimbabwe and Cote d‘Ivoire (2019)
The paucity of information on the age at which Forced Sexual Act (FSA) among women occur and the factors affecting the timings in Africa necessitated this study. We assessed the timing of first FSA and its prognostic factors among women in three African countries. We used sexual violence data of 18,528 women aged 15–49 years who participated in Zimbabwe (2011), Kenya (2014), and Cote d’Ivoire (2014) demographic and health surveys. The time of first FSA was censored as the current age of women who had not experienced FSA. Kaplan-Meier methods and Cox proportional hazard model were used at p = 0.05. The proportion who had ever experienced FSA was 13.9%, 21.7% & 27.2% while median time to FSA was 17, 20 & 18 years in Kenya, Zimbabwe, and Cote d’Ivoire respectively. The highest (41.8%) lifetime prevalence of forced sexual act was among divorced/separated women in Cote D’Ivoire. Women aged 15–19 years had earlier risk of FSA: Kenya (aHR = 3.60 (95% CI:2.43–5.34)), Zimbabwe (aHR = 2.91 (95% CI:2.32–3.65)), and Cote d’Ivoire (aHR = 2.72 (95% CI:2.22–3.33)) than women aged 40–49 years. Other significant prognostic factors of time of FSA are marital status, place of residence, employment status, religion, wealth index, and education. There are generational shifts in timing of first forced sexual act among women with girls born in the 1990s becoming victims at earlier ages than those born in the 1960s and 1970s. There is a need for a multi-sectoral approach to reduce the prevalence and halt the negative trend in forced sexual act in Africa.